Peningkatan Hasil Belajar Siswa Menggunakan Pendekatan Value Clarification Technique (VCT) Model Matriks di Sekolah Dasar - Satria Efendi; Reinita Reinita (e-Journal Inovasi Pembelajaran Sekolah Dasar, 2019)
This research is motivated not optimal implementation based learning characters in primary schools. The purpose of this study isdescribes improving student learning outcomes in an integrated thematic learning using Matrix Model VCT approach in primary schools. This study uses qualitative and quantitative approaches. This type of research is the Classroom Action Research (CAR). The subjects were students of class VB SDN 36 Cengkeh of Padang. The experiment was conducted in two cycles. The study design includes planning, implementation, observation, and reflection.The results showed: a) RPP first cycle 81% Cycle II 94% b) Implementation of the aspects of the teachers 'first cycle of 83%, the second cycle 94% c) Implementation of the aspects of the students' first cycle of 77% and Cycle II 94% d) the results of student learning the first cycle of obtaining an average value of 76, the second cycle 86. thus Matrix Model VCT approach can improve student learning outcomes in an integrated thematic learning in class VB SDN 36 Cengkeh of Padang.Keywords: Matrix Model VCT approach, learning outcomes.